Response to Donald et al., (2025) - Elaine Mitchell; Naoya Takeda; Liam Grace; Peter Grace; Ken Day; Sahar Ahmadi; Warwick Badgery; Annette Cowie; Aaron Simmons; Richard Eckard; Matthew Tom Harrison; William Parton; et al. (Carbon Management, 2025)
Donald et al. (2025) misinterpret the central premise of the paper, incorrectly stating that we argue “carbon credit claims […] for increased sequestered carbon from early measurements are based on increases related to favourable climatic variations rather than improved land management”. At no point in our paper do we make this claim. Instead, our analysis concluded that “SOC stocks were primarily driven by rainfall,” while also acknowledging the role of improved land management in SOC dynamics.